Strategy of PT.MARKTEL to Increasing Market Share - Hazazi, Rizka; Aditya Wibowo, Satya (The Indonesian Journal of Business Administration, 2016)
Abstract - Nowadays almost every countries including Indonesia have the problem with the poor traffic condition. The impact of bad conditions will lead to amount of problems, ecen increasing the number of accidents. To resolve this problem, improving the quality and quantitiy of the availability public transportation is become one of the solutions. Not only that, the application of the Intelligent Transportation System also become the solution that until know believed could improve the traffic condition, so many countries including Indoneisa currently many developed the system become the ITS.Â  The need of ITS in Indonesia has prompted PT. MARKTEL as one of manufacture traffic light product company to developed their product in order to supported the intergration system accordance to the condition and psychology ot he traffic Indonesia condition. Before PT. MARKTEL existed, Indonesia is the one of the big consumen of traffic light product system from Australia, SCATS. Almos every city in Indonesia apply this system, so SCATS has a larger market shared than PT. MARKTEL. PT. MARKTEL has a vision to become the best company in this industry. However, there are some problems that become a barriers for this company to achieve their goal. Base on internal and externam also SWOT analysis was found several problems that become a barrier for PT. MARKTEL to achieves their goal. These problem indirectly affected the marketing mix element of PT. MARKTEL. To response these problems, based on analysis conducted PT. MARKTEL need to improving their marketing strategy and reorganize internal condition.Â Keywords : Marketing strategy, ITS (Intelligent Transportation System), Traffic light, Marketing Mix